Sistema informático de gestión ganadera, para el procesamiento analítico en línea de información en la quinta experimental Punzara de la Universidad Nacional de Loja. - Castro Vásquez, Víctor Rodrigo (2016)
This final thesis work is aimed at improving the management and handling of livestock Cattle and Sheep on Fifth Experimental prick of the National University of Loja allowing better flow of information. It is in our area, where technological development more intensively studied, allowing us to optimize and improve the services provided to the university community, so that this work begins with a review of literature, which is detailed concepts and definitions necessary for the development of this work tools. Observation techniques on the Management and Administration that was used initially in the Fifth, and an interview with Dr. René Chamba charge of the Quinta Experimental prick, another method implemented was used for data collection, is the survey, it was applied to the administrative staff working in the Fifth, to continue the detail of the methodology used for the development of this work. The software development methodology used is ICONIX, for handling Events Livestock Management System Deterministic Finite Automata are used enabling execute processes based on a set time and an event previously executed. In the results section, shown as a first step analysis of the current situation where the requirements, constraints and design of this study limit switch as a second phase development Livestock Management System is exposed, exposed and third refers to the implementation phase, performance testing and validation, ended the conference for students in the career of Veterinary Medicine, National University of Loja. With this software is able to cover the activities of livestock management Cattle and Sheep Experimental performs prick Fifth National University of Loja, more quickly, effectively and reliably.